Correlation Between Learning Motivation and Satisfaction in Synchronous On-the-Job Online Training in the Public Sector - Chow, Nathan Cheng-Hu; Yeh, I-Jan (Frontiers in Psychology, 2022)
Non-governmental organizations, in order to achieve corporate sustainability, often regard expanding revenue and reducing costs as the standards and consider human resources as important assets of the company. Unlike non-governmental companies, government agencies present large flexibility on staffing. In regard to employees’ education and training in human resource strategies, the popularity of organizational learning in past years to train employees to create operational performance seems to be the panacea for corporate sustainability. Public sectors, along with such a trend, also establish many learning channels for employees, among which the curriculum development of synchronous online learning is worth noting. Aiming at supervisors and employees of Taipei City Government, as the research objects, total 360 copies of questionnaire are distributed, and 268 valid copies are retrieved, with the retrieval rate 74%. According to the results to propose discussions, it is expected to help public sectors enhance employees’ cohesiveness and further create operational team spirit.